Factors Influencing the Survival of Micro and Small Enterprises (MiSEs) in Thai Night Markets During an Economic Crisis - Chantith, Chaturaphat; Nookate, Pheerawas (Thailand and The World Economy, 2025)
This study investigated the factors influencing the survival of Micro and Small Enterprises (MiSEs) in the Greenway Night Market in Thailand during the COVID-19 pandemic. It employed OLS, Logit, and Ordered Logit regression models on data from 320 thriving MiSEs through structured questionnaires in late 2022. This approach contributed to understanding MiSEs’s resilience and informed policy development for future crises by selecting factors that had a statistically significant impact on survival and remained consistent across regression models with different thresholds. Findings revealed that, among the adaptive strategies, selling assets to enhance liquidity was crucial for survival, while seeking additional income and requesting debt deferrals negatively impacted business performance. The "50:50 co-payment" scheme and reduced utility costs were identified as effective government interventions. Future research was suggested to explore additional factors and assess policy impacts.